2020
DOI: 10.1123/jpah.2019-0357
|View full text |Cite
|
Sign up to set email alerts
|

Nordic Walking for Overweight and Obese People: A Systematic Review and Meta-Analysis

Abstract: Background: Nordic walking (NW) is a potentially beneficial exercise strategy for overweight and obese people. To date, no reviews have synthesized the existing scientific evidence regarding the effects of NW on this population. This systematic review and meta-analysis aimed to identify the characteristics, methodological quality, and results of the investigations that have studied the effects of NW in overweight and obese individuals. Methods: Six electronic databases were searched up to June 2019 for studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…This minimal difference in energy expenditure could explain how RW obtained slightly better results in the current study, underlining that NW has also shown improvements in this regard. These results are not in line with the fact that energy expenditure is higher in the NW pattern, and this would mean a greater body mass loss [ 28 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This minimal difference in energy expenditure could explain how RW obtained slightly better results in the current study, underlining that NW has also shown improvements in this regard. These results are not in line with the fact that energy expenditure is higher in the NW pattern, and this would mean a greater body mass loss [ 28 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Mejias-Pena et al (2016) did not record any change in the expression of TLR2, TLR4, MyD88, and TRIF, in peripheral blood mononuclear cells (PBMCs) from older subjects after 8 weeks of aerobic exercise training, suggesting the possibility that the type of exercise might be a determinant of the TLRs-mediated anti-inflammatory effect of exercise. The lack of control for confounding variables, in the available studies, prevents a definitive elaboration on potential benefits of this interventional practice, according to a recently published systematic review ( Sanchez-Lastra et al, 2020 ). However, Nordic walking is a potentially beneficial exercise strategy for overweight and obese people.…”
Section: Discussionmentioning
confidence: 99%
“…However, Nordic walking is a potentially beneficial exercise strategy for overweight and obese people. Based on the twelve good-to-fair quality selected studies, the authors of this study evidenced that subjects performing Nordic walking experienced significant improvement in parameters such as fasting plasma glucose, abdominal adiposity, and body fat compared with the values recorded at baseline, but no significant improvements were found when compared with control groups ( Sanchez-Lastra et al, 2020 ). Notably, adiposity in the elderly may be associated with a deregulated glucose metabolism, and hence to an increased risk of T2DM, via a deregulation of immune cells and, specifically of CD8+ cytotoxic subsets ( Bosslau et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…glucose control, cardio-respiratory fitness, flexibility and upper-body strength) than merely walking [ 25 , 26 ], and it is easier to perform than high-intensity interval training [ 27 ]. However, although NW seems to be more enjoyable than simply walking, the PA drop-out ratio remains high [ 24 ].…”
Section: Introductionmentioning
confidence: 99%